Initial experience of laparoendoscopic single-site radical prostatectomy with a novel purpose-built robotic system - Zheng Wang; Chao Zhang; Chengwu Xiao; Yang Wang; Yu Fang; Baohua Zhu; Shouyan Tang; Xiaofeng Wu; Hong Xu; Yi Zhou; Lingfen Wu; Zhenjie Wu; et al. (Asian Journal of Urology)
Objective: This prospective single-arm clinical trial aimed to evaluated the feasibility and safety of the application of the SHURUI system (Beijing Surgerii Technology Co., Ltd., Beijing, China), a novel purpose-built robotic system, in single-port robotic radical prostatectomy. Methods: Sixteen patients diagnosed with prostate cancer were prospectively enrolled in and underwent robotic radical prostatectomy from October 2021 to August 2022 by the SHURUI single-port robotic surgical system. The demographic and baseline data, surgical, oncological, and functional outcomes as well as follow-up data were recorded. Results: The mean operative time was 226.3 (standard deviation [SD] 52.0) min, and the mean console time was 183.4 (SD 48.3) min, with the mean estimated blood loss of 116.3 (SD 90.0) mL. The mean length of postoperative hospital stay was 4.50 (SD 0.97) days. Two patients had postoperative complications (Clavien-Dindo Grade II), and both patients improved after conservative treatment. All patients’ postoperative prostate-specific antigen levels decreased to below 0.2 ng/mL 1 month after discharge. The mean prostate-specific antigen level further decreased to a mean of 0.0219 (SD 0.0641) ng/mL 6 months after surgery. Thirty days postoperatively, 12 out of 16 patients reported using no more than one urinary pad per day, and all patients reported satisfactory urinary control without the need for pads 6 months after surgery. Conclusion: The SHURUI system is safe and feasible in performing radical prostatectomy via both transperitoneal and extraperitoneal approaches. Tumor control and urinary continence were satisfying for patients enrolled in. The next phase involves conducting a large-scale, multicenter randomized controlled trial to thoroughly assess the effectiveness and safety of the new technology in a broader population.